Biotechnological approaches on conversion of agrocellulosic residues and dairy wastes into useful end-products - SINGH, KISHAN (The Indian Journal of Animal Sciences, 2014)
Utilization of agrocellulosic residues and dairy waste is a major milestone in biotechnological generation for the production of valuable animal feed, food, energy and chemicals, In the tropical countries, especially the developing ones, there is a plenty of organic wastes which can profitably be used as value added products if appropriate technologies are effectively applied. The solid substrate/state fermentation (SSP) technology has very wide scope for enriched animal feed production. The combination of SSF and ensiling is a novel process that converts poor quality lignocellulosic materials into highly digestible animal feed, SSP with lignocellulolytic organisms increases the protein content of the product and partially degrades lignocellulose with enzymes produced during the fermentation, Ensiling, on the other hand, in the presence of such enzymes and lactic cultures (ENLAC) preserves the nutritional value of the feed and increases its digestibility and palatability, Keeping the 'threat of population explosion and protein crisis in view, microbial biomass proteine single-cell protein production from different organic residues may serve as good protein source and substrate in food or feed to meet the demands of protein requirements of the hunger and poverty-sticken nations. The fermentation of dairy effluent with yeast and bacteria and that of waste effluent with algal fermentation results in single-cell protein production which can be used as a supplementary food/feed. Success of the fermentations ultimately depends on adaptation to local conditions. Improvement of microbial strains by selection or genetic alteration is the province of the resident biologists, The potential ofthe described and other wastes should be exploited.